PS26 Prevalence and Associations of Limited Health Literacy in Chronic Kidney Disease: A Systematic Review. (17th September 2012) - Fraser, SDS; Roderick, PJ; Casey, M; Taal, MW; Yuen, HM; Nutbeam, D
Abstract : Background: Chronic kidney disease (CKD) is a prevalent and growing problem, strongly associated with obesity, diabetes, hypertension, and cardiovascular disease. Health inequalities are recognised throughout the CKD pathway, including prevalence of risk factors, prevalence of CKD, progression, and renal replacement therapy. There is evidence that an adequate level of health literacy (defined as 'the cognitive and social skills which determine the motivation and ability of individuals to gain access to, understand, and use information in ways that promote and maintain good health') contributes to improved disease management, and that inadequate health literacy is a potentially modifiable determinant of poor health outcomes and health inequalities in people with chronic disease. The aim of this review was to synthesise and critically appraise the literature evidence on the prevalence and associations of limited health literacy in CKD. Methods: Seven databases were searched using terms for CKD and health literacy (HL). Cross sectional studies, and baseline data from cohort and randomised controlled trials were included where they assessed and presented the prevalence of limited HL using a validated tool in adults with CKD of any stage. The primary outcome was an objectively measured prevalence of limited HL in a population with CKD. The secondary outcome was associations of limited HL. Study quality was assessed by two reviewers using standardised criteria. Prevalence values were combined using a random effect model to give overall prevalence. Results: 82 studies were identified from searching, of which six met the inclusion criteria. The total number of people with CKD in all studies was 1, 405. Five studies were in dialysis or transplant populations, and all were from the US. There was significant heterogeneity in the prevalence of limited HL (9% to 32% (median 25%, inter-quartile range 16%)). The pooled prevalence of limited HL in all studies was 22.7% (95% CI 20.6%, 24.8%). The review identified associations between limited HL and socioeconomic factors (lower education attainment, lower income), and certain process and outcome measures (lower likelihood of referral for transplant, higher mortality). Overall study quality was poor, with particular weaknesses of sampling and non-response. Conclusion: Limited health literacy is common among people with CKD and independently associated with socioeconomic factors and health outcomes. It may represent an important determinant of inequality of outcomes in CKD. There is a need for further investigation of limited health literacy in people with pre-end stage CKD, and in UK CKD populations.